Impact of Integrated Services on HIV Testing: A Nonrandomized Trial among Kenyan Family Planning Clients. Issue 2 (4th May 2017) - Church, Kathryn; Warren, Charlotte E.; Birdthistle, Isolde; Ploubidis, George B.; Tomlin, Keith; Zhou, Weiwei; Kimani, James; Abuya, Timothy; Ndwiga, Charity; Sweeney, Sedona; Mayhew, Susannah H.; ,
Abstract : The impact of integrated reproductive health and HIV services on HIV testing and counseling (HTC) uptake was assessed among 882 Kenyan family planning clients using a nonrandomized cohort design within six intervention and six "comparison" facilities. The effect of integration on HTC goals (two tests over two years) was assessed using conditional logistic regression to test four "integration" exposures: a training and reorganization intervention; receipt of reproductive health and HIV services at recruitment; a functional measure of facility integration at recruitment; and a woman's cumulative exposure to functionally integrated care across different facilities over time. While recent receipt of HTC increased rapidly at intervention facilities, achievement of HTC goals was higher at comparison facilities. Only high cumulative exposure to integrated care over two years had a significant effect on HTC goals after adjustment (aOR 2.94, 95%CI 1.73‐4.98), and programs should therefore make efforts to roll out integrated services to ensure repeated contact over time.